Challenges Faced by Anti-Terrorism Police Unit in Fighting Terrorism; A Case Study of Nairobi County, Kenya - Fredrick, Elijah Mwadori; Mwangi, Samson Wokabi; Mwaeke, Panuel (European Journal of Applied Sciences, 2023)
This study established the challenges faced by anti-terrorism police unit in fighting terrorism in Nairobi County, Kenya. The study has been motivated by increased public perceptions of anti-terror police ineffectiveness in the midst of rising terror related activities in Nairobi County, Kenya. Guided by this broad objective, the study examined the legal challenges faced by the Kenya anti-terrorism police unit in fighting terrorism in Nairobi County, established the technological challenges faced by an anti-terrorism police unit and examined the effect of corruption on war against terror within the Kenya anti-terrorism police unit in Nairobi County. The study was grounded by the Rational Choice Theory and adopted a case study qualitative design. The main method of data collection was the interview. The study comprised of 80 respondents: 76 main respondents and 4 Key Informants. Purposive sampling Method was used to select respondents for the study. Data was transcribed and the transcriptions coded using NVIVO software. Two major legal challenges identified were related to both Kenya constitution, Domestic and International Human Right laws. The study found that the war on terror is shrouded in ambiguities in interpreting the law on what terrorism is, biases in dealing with terror suspects and confusion on what international partners want. For example, anti-terrorist global pundits portend that governments should respond to this threat with maximum force to deter acts of terror, biases and contradictions with regard to the terrorists “the supreme right “with no derogation from this right while at the same time negating the “supreme right” of victims or rather other Kenyans. Further, constitutional rights and freedoms emerged as major challenge that hampered police operations and action. Further established technological skilled challenges faced by anti-terrorism police unit in Nairobi County include capacity to crack: Incitement Platforms, Terrorist Financing platforms and Websites used as online stores. Further, there is technological skill gap to enable them crack; encrypted, compressed and password-protected and anonymised terrorist materials, including documents and videos, which are then uploaded and circulated via the internet encryption software of terrorist Secrets” to facilitate covert internet communications. According to the third objective, terrorist criminal groups will always grease or oil the system right from the investigating agencies through the Judiciary to the prison. According to this study, fighting police corruption that hampers war on terror is a tall order because the real problem is public corruption. At times officers get a tip off about suspected terrorist activity somewhere but before they make a move a phone call from “above” or a politician disrupted with instructions to stand down. Presiding Judges and Magistrates are in most cases also compromised to snub most evidence in their ruling, most of it being digital or forensic and either throw away the cases leading to miscarriage of Justice or even incriminate them to prison where intended radicalization may have been planned. From there prison authorities may also be bribed to aid escape. Amongst other recommendations, A reviewed with regard to Legal rights and freedoms of accused and victims of terror related crimes in relations to the supreme right. This review should put safeguards and remove any legal challenges that may hamper war on terror. The anti-terror police unit should train all officers to catch up with new technology. Given its magnitude, winning the war on corruption may hence, require political will executive order or decree from a benevolent dictatorial presidency.